The Pharmacological Mechanisms of Anthocyanin in Aqueous Extract of Purple Sweet Potato as Antihyperglycemic Herbal Remedy (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: purple sweet potato; pancreatic #x3B2; -cell; diabetic rat